Use of a next-generation multi-durometer long guide sheath for triaxial access in flow diversion: experience in 95 consecutive cases. (14th July 2017) - Lin, Li-Mei; Bender, Matthew T; Colby, Geoffrey P; Beaty, Narlin B; Jiang, Bowen; Campos, Jessica K; Huang, Judy; Tamargo, Rafael J; Coon, Alexander L
Abstract : Background: Intracranial access techniques in modern neurointerventions have shifted towards more robust access platforms. The long guide sheath is one of the building blocks of triaxial systems used in intracranial embolizations. Here we present our experience with the AXS Infinity LS long sheath in the triaxial platform for the implantation of the Pipeline embolization device (PED). Methods: We retrospectively identified patients who underwent PED Flex treatment with the AXS Infinity LS at a single institution. Procedural data collected included parent artery tortuosity, patient demographics, vasodilator use, aneurysm characteristics, equipment utilized, and catheter-related complications. Results: A total of 95 cases were completed using the AXS Infinity LS for the triaxial platform foundation in PED Flex treatment of cerebral aneurysms. Mean patient age was 56.2±12.2 years (range 21–86). Average aneurysm size was 6.9±6.2 mm (range 1–38). There were 89 anterior circulation cases (94%) and 6 posterior circulation cases (6%). Significant cervical ICA tortuosity was present in 11/89 (12%) and moderate to severe cavernous ICA tortuosity was present in 29/89 (33%). Mean fluoroscopy time was 40.0±19.8 min. In 14/95 cases (15%), vasospasm prophylaxis or treatment with intra-arterial verapamil infusion was performed. Catheter access-related complications included asymptomatic iatrogenic dissection in one case (1%) from the distal intracranial catheter and groin hematoma in one case (1%). No parent vessel wall abnormalities were visualized in the region of the Infinity long sheath on final control angiography in all 95 cases. Conclusion: The AXS Infinity LS is the newest long guide sheath available for modern neurointerventional procedures. We have shown its utility in augmenting the triaxial access platform in PED Flex cases by providing enhanced distal tip trackability with added support in the aortic arch and proximal great vessels.